KAJIAN KEBUTUHAN AIR BERSIH PDAM NGANCAR KABUPATEN KEDIRI - Agus Ainur Rofiq; Lucia Desti Krisnawati; Sigit Winarto (Faculty of Engineering, Kadiri University, 2018)
The problem of providing clean water is now a very serious problem in Kediri Regency, especially in the Ngancar region. The purpose of this study is to predict the need for clean water for the service area of the Ngancar PDAM Kediri Regency in the next 10 years and analyze the availability of clean water from the Ngancar unit for the next 10 years using secondary data references from the PDAM of Kediri Regency. In calculations using linear regression formula. The results of this study are that the need for water in the service area of the Ngancar unit for 2026 with 3,431 customers and 80% service plan reaches Q = 79.25 lt / sec and the availability of raw water of the Ngancar unit for 2026 is 11.97 lt / det. So that the raw water source of the Ngancar unit can be used sustainably to meet the clean water needs of the Ngancar unit service area, it is necessary to optimize the raw water of the Ngancar unit by increasing the flow of old raw water sources with a larger discharge to maintain the stability of the discharge and reduce the level of leakage in distribution network. Masalah penyediaan air bersih saat ini menjadi permasalahan yang sangat serius di Kabupaten Kediri khususnya di wilayah Ngancar. Tujuan penelitian ini untuk memprediksikan kebutuhan air bersih untuk wilayah pelayanan unit PDAM Ngancar Kabupaten Kediri pada kurun waktu 10 tahun kedepan dan menganalisis ketersediaan air bersih unit Ngancar sampai 10 tahun kedepan dengan menggunakan acuan data sekunder dari PDAM Kabupaten Kediri. Dalam perhitungan menggunakan rumus regresi linier. Adapun hasil penelitian ini adalah bahwa kebutuhan air di wilayah pelayanan unit Ngancar untuk tahun 2026 dengan jumlah pelanggan 3,431 dan rencana pelayanan 80% mencapai sebesar Q = 79,25 lt/det dan ketersediaan air baku unit Ngancar untuk tahun 2026 sebesar 11,97 lt/det. Agar sumber air baku unit Ngancar dapat dimanfaatkan secara berkelanjutan untuk memenuhi kebutuhan air bersih wilayah pelayanan unit Ngancar, maka perlu tindakan optimalisasi air baku unit Ngancar dengan menambah debit sumber air baku yang lama dengan debit yang lebih besar untuk menjaga kestabilan debit dan mengurangi tingkat kebocoran pada jaringan distribusi.